Genetic modifiers of Hb F: The role of regulatory SNPs in β-Thalassemia phenotypic variability - Canatan, Duran; Altunsoy, Emel (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Gene modifiers affecting β-thalassemia are important for the patient’s phenotype. Primary modifiers are the location of mutations in β gene regions Secondary modifiers are coexistence α-globin chains, and third modifiers are single nucletotide polymorphisms (SNPs) on the effect of Hb F. The aim of this study is to investigate the effect of five important SNPs in modifier genes affecting Hb F level. Material and methods: A total of twenty-five cases, aged between 1-44 years (Mean±SD: 14.52±30.40), as four TDT, eighteen with NTDT and three with S+beta thalassemia were included in study. Five SNPs in beta modifier genes: HBG2:g-158(C>T), BCL11A: rs1427407 (G>T), BCL11A: rs10189857 (A>G), HBS1L-MYB : rs28384513 (A>C) and HBS1L-MYB: rs9399137 (T>C) were examined and compared effect on HbF. Results: A total of 50 SNPs were detected in 25 cases, found as 41 heterozygous and 9 homozygous polymorphisms The distribution of polymorphisms according to the cases, 4 polymorphisms (8%) were detected in S+Beta thalassemia, 5 polymorphisms (10%) in TDT, and 41 polymorphisms (82%) in NTDT. While the Hb F average of 13 cases (52%) with α and β coexistence was 78.2+28.9, the Hb F average of 12 cases (48%) without α and β coexistence was 44.4+57.2. Conclusion: It may contribute to the molecular mechanisms of HbF regulation. For this purpose, it is recommended to make a detailed molecular diagnosis of each patient with β-thalassemia, and to examine the modifier genes affecting the beta gene, as well as alpha and beta gene analyses.